(3GdYhdeI hGdghjI GdKbGajIs ((3GdbGgQI(B:s (3GdeLdS GdGYdj ddKbGaI(B,s)
(3GdYhdeI (B- (3GdchcHI (B- (3GdghjI GdhWfjI (B- (3GdghjI GdKbGajI(B- (3CReI GdghjI(B- (3GdYhdeI hGdghjI(B- (3GdYfa GdKbGaj ddYhdeI(B- (3GdYhdeI hBdjGJ GdJgejT aj GdKbGaI GdYQHjI(B- (3GdYhdeI hGdJOGYjGJgG GdEbJUGOjI hGdKbGajI(B- (3GdYQH heNGha GdYhdeIs
Keywords: (3GdKbGaI GdYQHjIs; (3GdYhdeIs